A comparative study of clinicopathological significance, FGFBP1, and WISP-2 expression between squamous cell/adenosquamous carcinomas and adenocarcinoma of the gallbladder - Yang, Zhulin; Yang, Zhi; Zou, Qiong; Yuan, Yuan; Li, Jinghe; Li, Daiqiang; Liang, Lufeng; Zeng, Guixiang; Chen, Senlin (International journal of clinical oncology, 2014)
Background The differences in clinical, pathological, and biological characteristics between adenocarcinoma (AC) and squamous cell/adenosquamous carcinoma (SC/ASC) of gallbladder cancer have not been well documented. This study is to compare the clinicopathological characteristics and FGFBP1 and WISP-2 expression between AC and SC/ASC patients. Methods We examined FGFBP1 and WISP-2 expression in 46 SC/ASC and 80 AC samples using immunohistochemistry and analyzed their correlations with clinicopathological characteristics. Results SC/ASCs occur more frequently in older patients and often correspond to larger tumor masses than ACs. Positive FGFBP1 and negative WISP-2 expression were significantly associated with lymph node metastasis and invasion of SC/ASCs and ACs. In addition, positive FGFBP1 and negative WISP-2 expression were significantly associated with differentiation and TMN stage in ACs. Univariate Kaplan–Meier analysis showed that either elevated FGFBP1 ( p < 0.001) or lowered WISP-2 ( p < 0.001) expression was closely associated with decreased overall survival in both SC/ASC and AC patients. Multivariate Cox regression analysis showed that positive FGFBP1 expression ( p = 0.001) or negative WISP-2 expression ( p = 0.035 for SC/ASC and p = 0.009 for AC) is an independent predictor of poor prognosis in both SC/ASC and AC patients. We also revealed that differentiation, tumor size, TNM stage, lymph node metastasis, invasion, and surgical procedure were associated with survival of both SC/ASC and AC patients. Conclusion Our study suggested that the overexpression of FGFBP1 or loss of WISP-2 expression is closely related to the metastasis, invasion and poor prognosis of gallbladder cancer.